2020
DOI: 10.1590/s1677-5538.ibju.2019.0331
|View full text |Cite
|
Sign up to set email alerts
|

The effects of menopause on the quality of life and longterm outcomes of transobturator tape treatment in women with stres urinary incontinence

Abstract: Purpose: We aimed to investigate the effects of menopause on long-term outcomes of transobturator tape (TOT) surgery. Materials and Methods: Patients who underwent TOT surgery were evaluated under two groups as postmenopausal and premenopausal. The International Consultation on Incontinence short-form questionnaire (ICIQ-SF), Incontinence Impact Questionnaire (IIQ-7) and Urogenital Distress Inventory-Short Form (UDI-6) questionnaires were completed by the patients at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Other studies using Safyre™ have found recurrent incontinence ranging from 17.6 -21% in up to 96 months of follow-up (13,21). Subjective success rate in the long-term follow-up was 68,7% in HMS and 79,3% in the Safyre™ group, which was lower than the reported by Kenton et al (79% -85%) or Sahin et al (88%) after 5 years (3,22). In fact, a decline in the mid-and long-term MUS treatment success has been repeatedly reported (23)(24)(25).…”
Section: Discussionmentioning
confidence: 62%
“…Other studies using Safyre™ have found recurrent incontinence ranging from 17.6 -21% in up to 96 months of follow-up (13,21). Subjective success rate in the long-term follow-up was 68,7% in HMS and 79,3% in the Safyre™ group, which was lower than the reported by Kenton et al (79% -85%) or Sahin et al (88%) after 5 years (3,22). In fact, a decline in the mid-and long-term MUS treatment success has been repeatedly reported (23)(24)(25).…”
Section: Discussionmentioning
confidence: 62%
“…Significant improvement was found as early as 1 year follow-up. There were no significant differences between pre-and post-menopausal patients in terms of TOT efficacy at both 1 and 5 years of follow-up, suggesting that transobturator tape surgery is an effective treatment for UI regardless of pre-or post-menopausal status [18].…”
Section: Ui (Urinary Incontinence)mentioning
confidence: 80%
“…O envelhecimento é identificado como um fator de alto risco associado à incontinência urinária, uma vez que o processo de menopausa resulta em níveis reduzidos de estrogênio, levando à diminuição da pressão máxima de fechamento uretral. Devido a esse fator, a população idosa experimenta uma redução significativa na capacidade da bexiga e na pressão do detrusor durante a micção, tornando os idosos o grupo mais suscetível à incontinência urinária, corroborando com média a idade obtida no presente estudo 17 .…”
Section: Discussionunclassified